A Conductive Network and Dipole Field for Harnessing Photogenerated Charge Kinetics. Issue 48 (27th September 2021) - Liu, Zhaoli; Zhang, Cui; Liu, Lizhi; Zhang, Tianshu; Wang, Jing; Wang, Rong; Du, Ting; Yang, Chengyuan; Zhang, Liang; Xie, Linxuan; Zhu, Wenxin; Yue, Tianli; et al.
Abstract: Photogenerated charge separation and directional transfer to active sites are pivotal steps in photocatalysis, which limit the efficiency of redox reactions. Here, a conductive network and dipole field are employed to harness photogenerated charge kinetics by using a Ti3 C2 /TiO2 network (TTN). The TTN exhibits a prolonged charge‐carrier lifetime (1.026 ns) and an 11.76‐fold increase in hexavalent chromium photoreduction reaction kinetics compared to TiO2 nanoparticles (TiO2 NPs). This super photocatalytic performance is derived from the efficient photogenerated charge kinetics, which is steered by the conductive network and dipole field. The conductivity enhancement of the TiO2 network is achieved by continuous chemical bonds, which promotes electron–hole (e–h) separation. In addition, at the interface of Ti3 C2 and TiO2, band bending induced by the dipole field promotes photogenerated electron spatially directed transfer to the catalytic sites on Ti3 C2 . This study demonstrates that a conductive network and dipole field offer a new concept to harness charge kinetics for photocatalysis. Abstract : The TiO2 network exhibits two orders of magnitude enhancement in electric conductivity, which will greatly suppress electron–hole (e–h) recombination by reducing the charge‐transfer resistance. In addition, 2D MXene induces a dipole at the interface. The dipole field pushes charge extraction and suppresses charge recombination by inducing band bending.